La cesión del impuesto sobre el valor añadido a las regiones españolas - Rodríguez, Isabel Gil (2023)
This article explores to what degree regions in Spain have managed to become involved in the sales tax. The re have been a great number of different proposals that aim to let regions have a say in this tax: collection, regulation or management. Different formulas that would allow regions to participate in the sales tax have been set forth: transfer, territoriali zed attribution, or participation in the total or partial collection; transfer of the collected product in the sales tax‘s retailer phase, coupled with (or not, according to some proposals) regulatory or administrative powers; or ex novo creation of a sing le-phase state tax on sales by retailers, created in order to be then transferred to regional entities. There have even been some proposals to create new regional taxes on the sales tax‘s retailer phase, or to establish a regional surcharge on the sales ta x‘s base during its retailer phase. Among these proposals, the one that prevailed understands the sales tax as a tax transferred by the central government to regional entities.